PENGARUH KINERJA LINGKUNGAN, GREEN ACCOUNTING DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan Terdaftar Di Bei Dan Mengikuti Proper 2020 Dan 2021) - , Al Azhar L, Chairul Amali ,Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this research is to analyse the effect of environmental performance , green accounting and firm size on financial performance (empirical study on companies listed on indonesia stock exchange and following PROPER year 2020 and 2021)". This research is a quantitative study using secondary data observed from the company's annual report. The population in this study is the companies listed on the Indonesia Stock Exchange and following PROPER  year 2020-2021. The sample in this study were 33 companies with a total sampel is 66 data. The sampling technique used was purposive sampling technique. The analytical method used is multiple linear regression. The results of this research indicate environmental performance, green accounting and firm size has no effect on financial performance because the value of thitung<ttabel with a significance value of >0.05. Keywords: Environmental Performance (PROPER), Green Accounting, Firm Size And Financial Performance (ROA).